Working Capital Management and Financial Performance of SMEs in Mbale City - Tabitha Marion Chebet (Uganda Christian University, 2024)
The main purpose of the study was to determine the effect of Working Capital Management on the Financial Performance of SMEs in Mbale City. The specific objectives were assess the influence of accounts payable management on the financial performance of small and medium enterprises in Mbale City, examining the influence of accounts receivables management on the financial performance of SMEs in Mbale City, to analyze the influence of cash management on the financial performance of SMEs in Mbale City. The study covered a period of 3 years and adopted descriptive research design. The data was collected from a sample of 66 respondents. The study revealed that cash management has a positive significant influence on financial performance and it explains variances in financial performance by up to 34.4% (adjusted R square=0.344). The evidence presented showed that account receivable management affects financial performance (F=54.784, Sig level=0.000). It was also revealed that credit management affects financial performance. The findings indicate that the model fits well and significantly explain the variations in financial performance as a result of credit management (F=20.553, P-value<0.01). It was also concluded that any increase in effort by SMEs to manage working capital, there would be an increase in financial performance. The study concluded that there is a significant and positive influence of credit management on financial performance. The study also portrays evidence that there exists positive significant relationship between account receivable management and financial performance of small and medium enterprises with in Mbale City. The study recommends that SMEs should increase on then time lag of clearing bills, SMEs should manage their accounts receivables, monitoring petty cash, more research into how the other components of working capital management affects the financial performance of SMEs.